Analisis Hukum Kendaraan Bermotor Pasca Penerapan Pasal 74 Undang-Undang Nomor 22 Tahun 2009 - Zaeni Aji Bakhtiar (Syntax Corporation Indonesia, 2024)
Article 74 of Law Number 22 of 2009 concerning Road Traffic and Transportation has underpinned the police's efforts in regulating the elimination of motor vehicles that do not meet operational standards. However, the implementation of this article often creates a legal dilemma for vehicle owners whose vehicles have been administratively abolished but still have a valid BPKB. This article explores the paradox between the legal and operational status of the vehicle, highlighting the discrepancy between the legality documents and the operational feasibility of the vehicle. Using Sudikno Mertokusumo's theory of legal certainty and Jeremy Bentham's theory of utilitarianism, this analysis seeks to provide recommendations for regulatory adjustments to address these disparities, ensure social justice, and improve compliance with safety and environmental standards. As a result, the application of Article 74 of Law Number 22 of 2009 concerning Traffic and Road Transportation to motor vehicles with BPKB which is declared